The More, The Better: “Do the Right Thing” For Natural Killer Immunotherapy in Acute Myeloid Leukemia - Parisi, Sarah; Lecciso, Mariangela; Ocadlikova, Darina; Salvestrini, Valentina; Ciciarello, Marilena; Forte, Dorian; Corradi, Giulia; Cavo, Michele; Curti, Antonio (Frontiers in Immunology, 2017)
Natural killer (NK) cells are circulating CD3- lymphocytes, which express CD56 or CD16 and an array of inhibitory receptors, called killer-cell immunoglobulin-like receptors (KIRs). Alloreactive KIR-ligand mismatched NK cells crucially mediate the innate immune response and have a well-recognized anti-tumor activity. Adoptive immunotherapy with alloreactive NK cells determined promising clinical results in terms of response in acute myeloid leukemia (AML) patients and several data demonstrated that response can be influenced by the composition of NK graft. Several data show that there is a correlation between NK alloreactivity and clinical outcome: in a cohort of acute myeloid leukemia patients who received NK infusion with active disease, more alloreactive NK cell clones were found in the donor repertoire of responders than in non-responders. These findings demonstrate that the frequency of alloreactive NK cell clones influence clinical response in AML patients undergoing NK cell immunotherapy. In this work we will review the most recent pre-clinical and clinical data about the impact of alloreactive NK cells features other than frequency of alloreactive clones and cytokine network status on their anti-leukemic activity. A better knowledge of these aspects is critical to maximize the effects of this therapy in acute myeloid leukemia patients.